In vitro antibacterial activity of ceftazidime/avibactam in combination against planktonic and biofilm carbapenemase-producing Klebsiella pneumoniae isolated from blood. (December 2020) - Papalini, Chiara; Sabbatini, Samuele; Monari, Claudia; Mencacci, Antonella; Francisci, Daniela; Perito, Stefano; Pasticci, Maria Bruna
Highlights: Between 2014 and 2019, a total of 4241 blood cultures resulted positive. From 4241 blood samples, 130 (3.1%) KPC-producing K. pneumoniae (KPC-Kp) were identified. More than 96% of KPC-Kp isolates were resistant to meropenem. Ceftazidime/avibactam + meropenem showed synergistic or additive antibacterial activity. Abstract: Objectives: The aim of this study was to report on in vitro tests of antibacterial activity of ceftazidime/avibactam in combination against planktonic or biofilm KPC carbapenemase-producing Klebsiella pneumoniae (KPC-Kp), the rate of KPC-Kp blood isolates in University of Perugia Hospital over a 5-year period, and their antimicrobial susceptibility patterns. Methods: The antibacterial activity of ceftazidime/avibactam in combination with other antimicrobials was assessed against planktonic and biofilm bacteria by Etest and checkerboard assay. A retrospective review of laboratory data was performed to evaluate the rate of KPC-Kp from blood samples and their antimicrobial susceptibility patterns. Results: Between 2014 and 2019, 130/4241 (3.1%) KPC-Kp were identified from blood cultures. Their rate increased from 2.3% in 2014–2015 to 4.5% over the last 3 years. Overall, 4.6% (6/130) of KPC-Kp isolates were susceptible to meropenem, 65.4% (85/130) to colistin, 65.1% (84/129) to tigecycline, 34.6% (45/130) to amikacin, 36.2% (42/116) to gentamicin, 40.2% (39/97) to fosfomycin and 91.5% (65/71) to ceftazidime/avibactam. Five of six ceftazidime/avibactam-resistant KPC-Kp were isolated from patients not treated with ceftazidime/avibactam. Synergism was detected both by Etest and checkerboard assay for the combination of ceftazidime/avibactam plus meropenem against planktonic isolates, whilst lower bactericidal activity was observed in biofilm KPC-Kp isolates. Conclusions: Our in vitro data suggest that the combination of ceftazidime/avibactam plus meropenem has a synergistic antibacterial activity against planktonic bacteria, whilst a lower activity was detected against biofilm, suggesting worse clinical outcomes whenever biofilm infections are present. Further analyses are required to confirm these results before extending them to clinical practice.